INITIAL PUBLIC OFFERING (IPO) PERUSAHAAN PERTAMBANGAN BATUBARA DAN HUKUM PASAR MODAL DI INDONESIA - Hartana (Ganesha Civic Education Journal, 2022)
The Capital Market is essentially a market that is not much different from Traditional markets that have been known so far, where there are traders, buyers, and also bargain price. Law Number 8 of 1995 concerning Capital Markets has outlined that the Capital Market has a strategic position in national economic development. The growth of a Capital Market is very depending on the performance of the securities company. To coordinate capital, technical support, and human resources in capital market development requires an effective leadership. Companies must cooperate closely to create a market that is able to provide various types of products and investment alternatives for the community. To develop the infrastructure for the securities industry requires substantial investment big. The investment depends on the economic benefits that can be earned by entrepreneurs. Factors that can reduce the investment amount that could be required to build infrastructure and reduce operating costs securities companies, will encourage the development of the Capital Market through improvement the survival of the Securities Company. This development can be achieved if these factors are also capable of producing services and alternatives safe investment and high quality especially in providing optimal service to investors so that its development later will greatly affect the interest of potential new investors who want to try investing in the Capital Market